KRITIK SOSIAL DALAM MEME MEDIA SOSIAL; KAJIAN WACANA PRAGMATIK - Kurniati, Titi; Murniasih, Siti; Rizal, Ghulam Arif (Universitas Peradaban, 2025)
This study aims to analyze the form of social criticism in memes circulating on social media using a pragmatic discourse approach. Memes as part of today's popular culture are not only used for entertainment, but also used as a medium for conveying social messages directly or implicitly. This study uses pragmatics theory, especially related to speech context, implicature, and speech acts, to see how criticism of social, political, economic, and cultural issues is packaged through a combination of text and images in memes. Data were obtained from various social media accounts that consistently upload memes with social criticism nuances. The method used in this research is descriptive qualitative. The results of the analysis show that memes are an effective medium of social criticism because they combine elements of satirical language, humor, and meaningful visual symbols. Thus, memes have an important role as an alternative means of communication in conveying public opinion or aspirations creatively and critically.